Quantifying the pollutant load into the Southern California Bight from Mexican sewage discharges from 2011 to 2020 - Arreola-Serrano, Ana S.; Mendoza-Espinosa, Leopoldo G.; Hernández-Cruz, Astrid; Daesslé, Luis W.; Villada-Canela, Mariana (Frontiers in Water, 2022)
Sewage discharges into the ocean are one of the main sources of pollutant load on the coasts, resulting in health risks and ecological deterioration. The Southern California Bight runs from Point Conception in California (USA) to Punta Colonet in Baja California (Mexico). The impact of U.S. sewage discharges on the bay is well documented, much less exist about the Mexican discharges. Official wastewater quality results for 17 wastewater treatment plants (WWTP) in Tijuana-Rosarito, Baja California from 2011 to 2020 are presented for the first time. Water quality was compared with the current Mexican Norm for the discharge of wastewater to the ocean. It was found that only 53% of the samples complied with all the normed parameters, while 88% complied specifically with trace metal concentrations. Among the parameters above the norm were fecal coliforms, total suspended solids, and chemical and biochemical oxygen demand (COD and BOD). The San Antonio de Los Buenos WWTP accounts for the discharge of 80% of the BOD for all Tijuana-Rosarito WWTPs, 76% of COD, 84% of total suspended solids (TSS), 54% of total nitrogen (TN), and 55% of total phosphorous (TP) to the ocean. These represent mean yearly discharges from 2011 to 2020 of 150 tons of TN, 27 tons of TP, 528 tons of TSS, 401 tons of BOD and 1191 tons of COD. Immediate action is needed to stop these high loads into the Pacific coast